Hedging using Derivatives: A Study of Non-Financial Firms in the UK - Smith, Christopher (2006)
Using data from annual reports for the fiscal year ending 2005, this paper presents evidence on the use of derivatives by non-financial firms in the United Kingdom. We find that non-financial firms generally only use derivatives for hedging purposes and that there is very little evidence of non-financial firms using derivatives for speculative purposes. Further, we find that derivative users and non-users differ in terms of a number of characteristics including firm size, capital structure and availability of internal funds. We also find evidence supporting the theory that information and transaction costs have a significant influence on the decision to use derivatives. Finally, other evidence suggests that one of the main motives for using derivatives is to reduce the probability and expected cost of financial distress.